Poland’s evolving Net Outward Investment Position : a cross-industry analysis - Gorynia, Marian; Nowak, Jan; Wolniak, Radosław (Economics and Business Review, 2008)
This study is a continuation of the authors' previous work on Poland's investment development path (IDP) and its geographic patterns. It examines changes in sector and industry composition of FDI inflows to and outflows from Poland and confronts the observed changes with the hypotheses derived from J. Dunning's model of IDP. The data time frame used (from 1996 to 2005) coincides with Poland's move through stage 2 of her IDP. The study reveals that during that stage a fundamental shift in sector/industry composition of FDI took place: the leading position of the manufacturing sector in both inflows and outflows was replaced by services (especially financial and trade). With respect to economic policy implications of the observed changes, the authors recommend a shift of focus from attracting FDI inflows towards stimulating outward FDI. (original abstract)